2004
DOI: 10.1063/1.1804245
|View full text |Cite
|
Sign up to set email alerts
|

Efficient organic solar cells by penetration of conjugated polymers into perylene pigments

Abstract: We report here efficient air-stable p-n heterojunction organic solar cells with a structure consisting of an n-type insoluble perylene pigment penetrated by a p-type-conjugated polymer, where the interfacial area for photocurrent generation increases. The solar cells are easily produced by infiltrating a soluble-conjugated polymer intentionally into an opening among insoluble microcrystalline perylene layer under a saturated chloroform vapor. This approach can be regarded as an alternative convenient way to ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 31 publications
1
25
0
Order By: Relevance
“…6,7 One notices that the efficiency decreases when LUMO p increases (i.e. the bandgap of the absorber increases), because less photons are being absorbed.…”
Section: Single Junction Organic Solar Cellmentioning
confidence: 99%
“…6,7 One notices that the efficiency decreases when LUMO p increases (i.e. the bandgap of the absorber increases), because less photons are being absorbed.…”
Section: Single Junction Organic Solar Cellmentioning
confidence: 99%
“…[7][8][9][10][11] For example, we reported that the ITO/amorphous TiO x / PCBM:P3HT/PEDOT:PSS/Au inverted type cell showed the power conversion efficiency of 2.47% and the performance of the cells with sealing was about the same after continuous light irradiating for 120 h in an ambient atmosphere. 12 Even without sealing, this solar cell maintained the performance after continuous light irradiation for 20 h. Thus, we have the techniques required to fabricate the organic thin-film solar cells with reasonable performance and stability.…”
Section: Introductionmentioning
confidence: 99%
“…In our previous research, we have developed organic thin film solar cells using a non-corrosive Au metal as the back electrode, and an ITO/In or a transparent conducting oxide (TCO)/TiO 2 as the front electrode [16][17][18][19]. We reported that the ITO/In/perylene tetracarboxylic derivative/poly(phenylenevinylene) derivative/PEDOT:PSS/Au two-layer type cell showed the power conversion efficiency of 1.9 % and its performance was about the same after irradiating for 1 h in an ambient atmosphere [20]. Thus, we have reported previously that an organic solar cell using a …”
Section: Introductionmentioning
confidence: 99%